Analysis Of The Influence Of Compensation, Flexibility, And Work Discipline On The Performance Of Online Ojek Drivers In Medan City - Estephania Tjuaca; Purnama Yanti Purba; Nerissa Evelyn; Shinta Arnela Sirait; Edi Cahyono (Cita konsultindo, 2024)
The objective of this study is to assess the impact of remuneration, work flexibility, and work discipline on the efficiency of online motorbike taxi drivers in Medan. This research is based on the growing popularity of online motorbike taxi services in Medan, which can be easily ordered through smartphone applications at any time and place. Additionally, preliminary interviews with drivers have revealed that compensation factors play a role in their work performance. This research utilized quantitative approaches and collected samples from the community of online motorbike taxi drivers in Medan. The sample method employed was accidental sampling, with a total of 102 respondents who were drivers. The data analysis strategy employs the method of multiple linear regression. The research findings suggest that salary does not have a partially significant impact on driver performance. However, job flexibility and discipline have a positive and substantial influence on enhancing driver performance in Medan. Ultimately, the combination of remuneration, adaptability, and work ethic has a constructive and noteworthy influence on enhancing the productivity of online motorcycle taxi drivers in Medan.